Preliminary Findings of Similarities and Differences in the Signed and Spoken Language of Children with Autism - Shield, Aaron (Seminars in Speech and Language, 2014)
Approximately 30% of hearing children with autism spectrum disorder (ASD) do not acquire expressive language, and those who do often show impairments related to their social deficits, using language instrumentally rather than socially, with a poor understanding of pragmatics and a tendency toward repetitive content. Linguistic abnormalities can be clinically useful as diagnostic markers of ASD and as targets for intervention. Studies have begun to document how ASD manifests in children who are deaf for whom signed languages are the primary means of communication. Though the underlying disorder is presumed to be the same in children who are deaf and children who hear, the structures of signed and spoken languages differ in key ways. This article describes similarities and differences between the signed and spoken language acquisition of children on the spectrum. Similarities include echolalia, pronoun avoidance, neologisms, and the existence of minimally verbal children. Possible areas of divergence include pronoun reversal, palm reversal, and facial grammar.
Keywords: Sign language; autism; language acquisition; echolalia; pronouns